Islamic Counseling Using the Exemplary Stories of the Prophet Muhammad to Improve the Manners of Elementary School Students - Mohammad Amin; Mohammad Thohir (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2026)
This study aims to determine how the application of Islamic counseling using the role model technique can improve the morals and manners of elementary school students. The background to this study stems from the persistent lack of respect for teachers and peers, as well as the failure to demonstrate politeness in speech and actions. Through exemplary stories of the Prophet Muhammad (peace be upon him) and Islamic figures, students are expected to emulate the good behaviors reflected in the stories. The method used in this study was a qualitative case study approach. Data were obtained through observation, interviews, and documentation, then analyzed descriptively using the steps of data reduction, data presentation, and drawing conclusions. The study subjects consisted of several students who experienced difficulties in maintaining good manners during interactions at school. The results showed that the application of the role model technique in Islamic counseling resulted in positive changes in student behavior. They became more polite, respected teachers, and behaved better towards their peers. Thus, the role model technique can be used as an effective method for developing morals in elementary school students.